Distributed denial of service attacks – holding back the flood. Issue 3 (March 2016) - Larson, Dave
Abstract : Today's Distributed Denial of Service (DDoS) attacks are almost unrecognisable from the basic volumetric attacks of old. In their early days the aim was simply to deny service to the Internet by bombarding it with traffic, designed to overload a server and render it out of action. But today's attacks have evolved to become more sophisticated and capable of carrying out several functions at once – they might bring a firewall down with a volumetric attack and then infiltrate the network to steal sensitive data while IT teams are distracted.